2022
DOI: 10.1039/d2tc00903j
|View full text |Cite
|
Sign up to set email alerts
|

Bright and stable quaternary ammonium antimony halides for solid-state lighting

Abstract: Lead halide perovskite, as a promising luminescent material, has been studied extensively in recent years. However, the toxicity of lead and its reduced duration and color stability under operating conditions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…This issue can be addressed by introducing a stereochemically active 5s 2 lone pair through Sb 3+ doping, which permits a stable host with flexible PL performance. As demonstrated in previous studies, versatile coordination modes have been observed for the highly emissive antimony halides , and Sb 3+ -doped metal halide compounds. ,, …”
Section: Introductionsupporting
confidence: 52%
“…This issue can be addressed by introducing a stereochemically active 5s 2 lone pair through Sb 3+ doping, which permits a stable host with flexible PL performance. As demonstrated in previous studies, versatile coordination modes have been observed for the highly emissive antimony halides , and Sb 3+ -doped metal halide compounds. ,, …”
Section: Introductionsupporting
confidence: 52%
“…In addition, the obtained device also exhibits a high luminous efficiency of 30.9 lm W À1 , which is comparable to other lead-free metal halides, such as (C 25 H 22 P) 2 -SbCl 5 (31.2 lm W À1 ), 49 [Na(DMSO) 2 ] 3 SbBr 6Àx Cl x (25.2 lm W À1 ) and [C 16 H 33 (CH 3 ) 3 N] 2 SbCl 5 (24.5 lm W À1 ). 51,52 Also noteworthy, the asfabricated WLED shows good color stability under different current drives (Fig. 6c), and thus Sb-doped (DPG) 3 InBr 6 has great application potential in SSL.…”
Section: Njc Papermentioning
confidence: 95%
“…Quaternary ammonium salts are cationic compounds containing alkyl groups in different lengths of carbon chains (usually including one or two long carbon chains and three or two short carbon chains), which are water soluble and can be used as disinfectants in textile industries. [48][49][50][51] Among then, double-chain didodecyldimethylammonium bromide (DDAB) has electrovalent bond and two long carbon chains, making it become an ideal substitute for OA/OAm ligands. [52][53][54][55][56] Although DDAB have been used as ligand for the synthesis of CsPbBr 3 and CsPbI 3 PNCs, few results were shown used for cyan PNCs yet.…”
Section: Resultsmentioning
confidence: 99%